Importance of Environmentally Managerial Accounting to Environmental and Economic Performance - Huynh, Quang Linh; Lan, Tran Thi Ngoc (International Journal of Energy Economics and Policy, 2021)
The role of environmentally managerial accounting between environmental performance and economic performance has been investigated in the current project. On the one hand, this project tried to re-examine the causal links among environmentally managerial accounting, environmental performance and economic performance that have been discussed in previous research; on the other hand, it also explored the moderation of environmentally managerial accounting between environmental performance and economic performance that has been overlooked. The data was collected from 298 publicly listed enterprises in Vietnam’s three main stock exchanges. To test the causal linkages, multiple regression analyses were employed; whereas to test the moderating effect, hierarchical regression analyses with the interaction were undertaken. The results indicate positive influences of environmentally managerial accounting on economic performance and environmental performance that in turn puts a positive impact on economic performance. The adoption of environmentally managerial accounting in business is revealed as a moderator between economic performance and environmental performance. The causal link from environmental performance to economic performance becomes tougher when enterprises take more environmentally managerial accounting into consideration in business. Keywords: Environmentally Managerial Accounting, Environmental Performance, Economic Performance, Vietnam JEL Classifications: Q01, Q51, E01 DOI: https://doi.org/10.32479/ijeep.11511